ROLE AND FUNCTIONS OF THE RUSSIAN LANGUAGE IN THE CONDITIONS OF SOVEREIGN UZBEKISTAN - Zakira Beketovna Nurgizarova (Web of Journals Publishing, 2023)
The Russian language in Uzbekistan implements linguistic communication among the multinational population. Knowledge of the Russian language affects career growth for every person.
Keywords: Russian language, language situation, intercultural communication, language community.